Pengaruh Kualitas Produk dan Lokasi terhadap Keputusan Pembelian pada Gudang Telur Siska Farm di Jorong Tiga Alur Kecamatan Harau - Hidayatul Arif; Amsah Hendri Doni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study addresses the decline in purchasing levels at Siska Farm Egg Warehouse over the past five years, which is assumed to be influenced by inconsistent product quality and limited accessibility of the business location. The purpose of this research is to examine the effect of product quality and location on purchasing decisions. This study employs a quantitative approach using primary data collected through questionnaires distributed to 94 respondents selected using the Slovin formula. The data were analyzed using multiple linear regression with the assistance of SPSS version 31, including validity, reliability, and classical assumption tests. The results indicate that product quality has a significant positive effect on purchasing decisions (p = 0.001), as well as location (p = 0.003). Simultaneously, both variables also show a significant effect on purchasing decisions, as indicated by the F-test (p = 0.001). The coefficient of determination (R²) shows that 28% of purchasing decisions are influenced by product quality and location, while the remaining 72% is explained by other factors not examined in this study. These findings suggest that improving product quality and accessibility can enhance consumer purchasing decisions.